Handbook of Camera Monitor Systems The Automotive Mirror-Replacement Technology based on ISO 16505 - Terzis, Anestis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This handbook offers a comprehensive overview of Camera Monitor Systems (CMS), ranging from the ISO 16505-based development aspects to practical realization concepts. It offers readers a wide-ranging discussion of the science and technology of CMS as well as the human-interface factors of such systems. In addition, it serves as a single reference source with contributions from leading international CMS professionals and academic researchers. In combination with the latest version of UN Regulation No. 46, the normative framework of ISO 16505 permits CMS to replace mandatory rearview mirrors in series production vehicles. The handbook includes scientific and technical background information to further readers' understanding of both of these regulatory and normative texts. It is a key reference in the field of automotive CMS for system designers, members of standardization and regulation committees, engineers, students and researchers.
Automotive Mirror-Replacement by Camera Monitor Systems -- Standardization and Vehicle Regulation Aspects of Camera Monitor Systems -- Resolution and Sharpness Requirements for CMS -- Vision in Commercial Vehicles with Respect to CMS -- Image Sensors for Camera Monitor Systems -- Optical Effects in Camera Monitor Systems -- Camera-Monitor-Systems as Solution for the Automotive Market -- Video Interface Technology -- Human Visual Perception -- A Camera-Monitor-System optimized to Humans - Fundamentals of Optical Perception and Requirements for Mirror Replacements on Commercial Vehicles -- Ergonomic Design of Camera-Monitor Systems in Heavy Commercial Vehicles -- Camera-Monitor Systems as a Replacement for Exterior Mirrors in Cars and Trucks -- CMS Concept for Commercial Vehicles - Optimized Fuel Efficiency and Increased Safe Mobility -- Optimization of Demanding Scenarios in CMS and Image Quality Criteria -- Intuitive Motion and Depth Visualization for Rear-View Camera Applications -- Functional Safety of Camera Monitor Systems.
Keywords: Signal processing; Automotive engineering; User interfaces (Computer systems).; Human-computer interaction; Signal, Speech and Image Processing; Automotive Engineering; User Interfaces and Human Computer Interaction